Involvement of Nuclear Factor Kappa B in High-Fat Diet-Related Pancreatic Fibrosis in Rats - Yan, Ming-Xian (The Korean Society of Gastroenterology; the Korean Society of Gastrointestinal Endoscopy; the Korean Association for the Study of the Liver; the Korean Society of Neurogastroenterology and Motility; Korean Association for the Study of Intestinal Diseases; Korean College of Helicobacter and Upper Gastrointestinal Research; Korean Pancreatobiliary Association; Korean Society of Gastrointestinal Cancer, 2012)
BACKGROUND/AIMS: High-fat diets contribute to pancreatic fibrogenesis, but the pathogenesis remains unclear. This study investigated the role of nuclear factor kappa B (NF-κB) in high-fat diet-induced pancreatic fibrosis in rats. METHODS: Male Wistar rats were fed a high-fat diet or standard normal chow for 20 weeks. Pancreatic fibrosis was determined by Sirius red staining. Immunohistochemical staining, reverse transcription-polymerase chain reaction and Western blotting were used to identify NF-κB-associated genes or protein expressions. RESULTS: Inflammation, fat deposition, pancreatic stellate cell activation and fibrosis were observed in the pancreases of the high-fat diet group. NF-κB subunit p65 (NF-κB/p65) expression was localized to the nucleus, and intercellular adhesion molecule 1 (ICAM-1) was over-expressed. Pancreatic gene expression levels of NF-κB/p65, ICAM-1 and tumor necrosis factor α were all elevated significantly in rats fed a high-fat diet compared with control rats. Western blotting also revealed significantly increased levels of ICAM-1 and nuclear NF-κB/p65 in rats fed high-fat diets comparison with control rats. CONCLUSIONS: NF-κB is involved in high-fat diet-related pancreatic fibrosis.